2017
DOI: 10.15740/has/au/12.techsear(3)2017/635-640
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis for prediction and classification of farmers based on adoption of drought coping mechanisms

Abstract: SUMMARY :The study was carried out to develop the classificatory statistical model to predict and classify the farmers into adopters and non-adopters in Kolar district of Karnataka for the year 2013. Linear discriminant analysiswas carried out by considering the various socio-economic characteristics of farmers as predictors and adoption behaviour of the farmers as response variable in order to assess the factors influencing on adoption of drought coping mechanisms. The result shows that the Box's M test is 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…This implies that the farmers who enjoy better access to climate change information (i.e., seasonal or mid-term forecasting) made betterinformed adaptation decisions. These findings were similar to the findings from various studies (Belay et al, 2017;Halagundegowda et al, 2017;Adeagbo et al, 2021;Tshikororo et al, 2021). As expected by the researchers, education and livestock rearing had a positive association across all climate change adaptation strategies.…”
Section: Determinants For Climate Change Adaptation Strategiessupporting
confidence: 91%
See 1 more Smart Citation
“…This implies that the farmers who enjoy better access to climate change information (i.e., seasonal or mid-term forecasting) made betterinformed adaptation decisions. These findings were similar to the findings from various studies (Belay et al, 2017;Halagundegowda et al, 2017;Adeagbo et al, 2021;Tshikororo et al, 2021). As expected by the researchers, education and livestock rearing had a positive association across all climate change adaptation strategies.…”
Section: Determinants For Climate Change Adaptation Strategiessupporting
confidence: 91%
“…This indicates the product-moment correlations between the discriminating variables and discriminant function. Factor loadings of ≥0.30 were used as the cutoff between important and less important variables, that is, if the structure coefficient was ≥0.30, it was considered meaningful (Duong et al, 2017;Halagundegowda et al, 2017;Kumari et al, 2017). The findings indicated that the structure coefficients with the highest relationship to function 1 were OFFI (0.846), FI (0.789), and FE (0.730).…”
Section: Structure Matrixmentioning
confidence: 99%
“…This implies that the farmers who enjoy better access to climate change information (i.e., seasonal or midterm forecasting) made better informed adaptation decisions. These ndings are similar to the ndings from various studies(Adeagbo, 2021;Halagundegowda, 2017;Tshikororo, 2021). As expected by the researchers, EDU and livestock rearing had a positive association across all climate-change adaptation strategies.…”
supporting
confidence: 91%
“…A high canonical correlation coe cient (0.948) indicates a function that discriminates well between two categories of dependent variable and also infers no overlapping among them. Squaring the canonical correlation suggested that 89.8 per cent of the variation in the grouping variable was explained (Halagundegowda, 2017;Nguyen, 2017). As shown through Table 4, unexplained error is 10.2 per cent (Wilks' λ: 0.102).…”
Section: Empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation